Dual kidney transplantation from uncontrolled deceased donors after cardiac arrest: A possible option. (15th August 2013) - Hanf, William; Petruzzo, Palmina; Meas‐Yedid, Vannary; Berthiller, Julien; Martin, Xavier; Morelon, Emmanuel; Badet, Lionel; Codas, Ricardo
Abstract Organ shortage is a major problem in organ transplantation. For this reason, transplantation teams have found it necessary to revisit their organ acceptance criteria. Uncontrolled deceased donors after cardiac arrest could increase the donor pool by 20%, but at the same time there is a greater risk of delayed graft function and primary non‐function. Dual kidney transplantation is an option when single kidney transplantation cannot be carried out because of lack of organ quality. We report for the first time our four first dual kidney transplantation from uncontrolled deceased donors after cardiac arrest with a follow up longer than 1 year. We described graft outcomes until 5 years, and histology at 3 and 12 months after transplantation. All organs were machine perfused in order to assess their quality leading to a single kidney transplantation or dual kidney transplantation decision. After 1 year of follow up, all grafts were functional with a mean estimated glomerular filtration rate of 44.5 ± 3.3 mL/min/1.73 m2, and a mean inulin clearance of 43.7 ± 13.6 mL/mn/1.73 m2. These findings suggest that dual kidney transplantation can represent a viable option for kidneys unsuitable for single kidney transplantation without increasing the rate of surgical complications. Successful transplantation is linked to histological, biological and donor clinical criteria, as well as perfusion parameters.